2006
DOI: 10.1111/j.1479-828x.2006.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of self‐reported alcohol intake among women attending for antenatal care in Far North Queensland

Abstract: Alcohol consumption during pregnancy is common in Far North Queensland. Methods currently used during antenatal booking visits to determine alcohol consumption before and during pregnancy are unreliable. Strategies to identify women consuming alcohol before and during pregnancy and education programs are vitally important if the incidence of fetal alcohol syndrome and spectrum disorder is to be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…These trends are particularly concerning as they are associated with a high prevalence of drinking during pregnancy [62,63]. These factors and the high rate of unplanned pregnancies [26,58], will account for some of the high prevalence of prenatal alcohol consumption in Australia [26,[64][65][66][67][68][69][70] and overseas [28,29,[51][52][53]60,71]. The reality is that many pregnancies will be exposed to alcohol prior to pregnancy awareness and for many the level of exposure will be very high.…”
Section: Risk and Perception Of Riskmentioning
confidence: 99%
“…These trends are particularly concerning as they are associated with a high prevalence of drinking during pregnancy [62,63]. These factors and the high rate of unplanned pregnancies [26,58], will account for some of the high prevalence of prenatal alcohol consumption in Australia [26,[64][65][66][67][68][69][70] and overseas [28,29,[51][52][53]60,71]. The reality is that many pregnancies will be exposed to alcohol prior to pregnancy awareness and for many the level of exposure will be very high.…”
Section: Risk and Perception Of Riskmentioning
confidence: 99%
“…Self‐reported alcohol consumption was classified as none, mild, moderate or heavy according to the criteria shown in Table 1, and consistent with findings reported from CBH in 2006 13 . These data were blinded as to case/control status and tested for consistency by a medical staff member of the Alcohol, Tobacco and Other Drug Use Service (ATODS) at CBH.…”
Section: Methodsmentioning
confidence: 95%
“…These communities also receive antenatal care services from the CBH Flying Remote Obstetric and Gynaecological Service (FROGS) and the majority of births to women from these communities take place in CBH. As reported elsewhere, all women booking for antenatal care with our service are asked about alcohol intake prior to pregnancy and after the diagnosis of pregnancy has become known to them 13 . It was decided to review the case notes of all mothers of children diagnosed with FAS by the POS to determine whether maternal high‐risk factors for FAS could be identified using our current antenatal care procedures, or whether tools shown to be useful elsewhere might be appropriate 14,15 .…”
mentioning
confidence: 99%
“…Another limitation of this study is the inability to compare study results to those of other studies because of the lack of a standardised measure for alcohol consumption in pregnancy. This is evident when comparing a study which reported 52.2% of women consuming alcohol at-least once during their pregnancy (Rimmer and de Costa, 2006) to this study's at-least weekly use of alcohol measure of 5.9%. Finally, debate continues about the accuracy of self-report of substance use by pregnant women in particular women's report of alcohol consumption, which like tobacco use in pregnancy has become socially unacceptable.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
“…Reports suggest the proportion of women consuming alcohol prior to pregnancy recognition can be high (Ethen et al, 2009, Ho andJacquemard, 2009) but it does decline greatly during pregnancy (Anderson et al, 2006, Ethen et al, 2009, Ho and Jacquemard, 2009, Rimmer and de Costa, 2006, Parackal et al, 2013. Reports on the characteristics of those women who continued to drink alcohol during pregnancy differ considerably.…”
Section: Scope Of the Problemmentioning
confidence: 99%